2020
DOI: 10.3389/fphar.2020.00399
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Small Molecule Compound Chrysin Promotes the Self-Renewal of Hematopoietic Stem Cells

Abstract: There is an increasing demand for the expansion of functional human hematopoietic stem cells (hHSCs) for various clinical applications. Based on our primary screening of antioxidant small molecule compounds library, a small molecule compound C2968 (chrysin) was identificated to expand cord blood CD34 + cells in vitro. Then we further verified the optimum concentration and explored its effect on hHSCs phenotype and biological function. C2968 could significantly increase the proportion and absolute number of CD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…In addition, Nrf-2, a major sensor/regulator of the cellular oxidative metabolism, is involved in the maintenance of HSC function [19], emphasizing the importance of energy metabolism in HSC biology. In line with this, several studies have demonstrated the capacity of exogenous antioxidant molecules to enhance the maintenance of HSC during ex vivo culture [20,21].…”
Section: Introductionmentioning
confidence: 77%
“…In addition, Nrf-2, a major sensor/regulator of the cellular oxidative metabolism, is involved in the maintenance of HSC function [19], emphasizing the importance of energy metabolism in HSC biology. In line with this, several studies have demonstrated the capacity of exogenous antioxidant molecules to enhance the maintenance of HSC during ex vivo culture [20,21].…”
Section: Introductionmentioning
confidence: 77%
“… Target/signaling Expansion effect Ref. Rapamycin mTOR 112 Garcinol/isogarcinol HATs 4.5-/7.4-fold HSCs 2.5-fold SRCs (garcinol) 118 TSA HDAC 2.5-fold CD34 + 40-fold CD34 + CD90 + 132 EchA ROS inhibition PI3K/AKT activation 1.33-fold CD34 + 1.7-fold CFUs 137 ASPP049 Hippo signaling ∼1.5-fold CD34 + CD38 − ∼2-fold hCD45 + 143 Chrysin p19, p57, MNDA, NR4A2, HOXB4 ∼1.5-fold HSCs 2.7-fold SRCs 145 Resveratol 1.84-fold CD34 + /CD133 + 138 , 139 , 140 CAPE HIF-1 α , SDF-1 α and VEGF-A 1.47-fold CFUs 1.77-fold SRCs 141 , 142 5-HT Apoptosis inhibition 1.73-fold CFU-F 12.2-fold CD34 + 146 α -Tocopherol ERK1/2 2-fold LSKs 147 ATRA RA receptor 4-fold CFUs 148 , 149 …”
Section: Small Molecules For Ex Vivo Hsc Expansionmentioning
confidence: 99%
“…It acts as an antioxidant to exert anti-tumor effects in several cancers, with several signaling been affected, such as MAPK and PI3K/AKT 144 . Screened from 85 antioxidant small molecules, chrysin was identified to expand HSC effectively and promote rapid engraftment in NOG mice, which might be attributed to its antioxidant-effect 145 . All discussed natural products are summarized in Table 3 .…”
Section: Small Molecules For Ex Vivo Hsc Expansionmentioning
confidence: 99%
“…Ex vivo expansion of CB stem cells is one of the most attractive strategies to enhance graft performance. A number of methods for ex vivo expansion, such as Notch-mediated expansion [43][44][45], MSC coculture [46,47], nicotinamide [48][49][50], StemRegenin-1 [51,52], copper chelation [53,54], chrysin [55], and UM171 [56,57], have been explored and some of them have already been tested in clinical trials (Table 1) Unmanipulated unit plus expanded unit; b) Stand-alone graft; c) Smaller expanded portion plus larger unmanipulated portion; d) Mean value.…”
Section: Ex Vivo Expansion Of Cb Stem Cellsmentioning
confidence: 99%